Opportunities for Honey Business to Influence the Family Economy in Hitigima Village, Assotipo District, Jayawijaya Regency - Defran Siska; Tukijan Tukijan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
“Opportunities for Honey Business to Influence the Family Economy in The Hitigima Village, Assotipo District, Jayawijaya Regency”  The aim of the research is to investigate the degree to which honey business opportunities contribute to the influence of the family economy in Hitigima Village, Assotipo Disctrict,  Jayawijaya Regency. The indicators considered are the following: production factors, production processes, and the economic worth of honey. The sample size for this research was 13. Observation, questionnaires, and literature reviews are used to collect data. The score analysis technique was utilized to analyze the data in this study. The results indicate that the honey business represented a significant opportunity for the influence of the family economy in Hitigima Village, Assotipo District, Jayawijaya Regency. The constraints include a lack of permanent honey sales and a little amount of honey production.